Digital Heritage. Progress in Cultural Heritage: Documentation, Preservation, and Protection 6th International Conference, EuroMed 2016, Nicosia, Cyprus, October 31 - November 5, 2016, Proceedings, Part II - Ioannides, Marinos; Fink, Eleanor; Moropoulou, Antonia; Hagedorn-Saupe, Monika; Fresa, Antonella; Liestøl, Gunnar; Rajcic, Vlatka; Grussenmeyer, Pierre (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2016)
This two-volume set LNCS 10058 and LNCS 10059 constitutes the refereed proceedings of the 6th International Conference on Digital Heritage, EuroMed 2016, held in Nicosia, Cyprus, in October/November 2016. The 29 full papers, 44 project papers, and 32 short papers presented were carefully reviewed and selected from 502 submissions. The papers are organized in topical sections on 3D Reconstruction and 3D Modelling; Heritage Building Information Models; Innovative Methods on Risk Assessment, Monitoring and Protection of Cultural Heritage; Intangible Cultural Heritage Documentation; Digital Applications for Materials' Preservation and Conservation in Cultural Heritage; Non-Destructive Techniques in Cultural Heritage Conservation; Visualisation, VR and AR Methods and Applications; The New Era of Museums and Exhibitions: Digital Engagement and Dissemination; Digital Cultural Heritage in Education, Learning and Training; Data Acquisition, Process and Management in Cultural Heritage; Data, Metadata, Semantics and Ontologies in Cultural Heritage; Novel Approaches to Landscapes in Cultural Heritage; Digital Applications for Materials' Preservation and Conservation in Cultural Heritage; and Serious Games for Cultural Heritage.